Fasting as an Adjuvant Therapy for Cancer: Mechanism of Action and Clinical Practice - Yichun Xie; Huabin Ye; Zhongjun Liu; Zhiqing Liang; Jinrong Zhu; Rongxin Zhang; Yan Li (Biomolecules)
The fundamental biological characteristics of tumor cells are characterized by irregularities in signaling and metabolic pathways, which are evident through increased glucose uptake, altered mitochondrial function, and the ability to evade growth signals. Interventions such as fasting or fasting-mimicking diets represent a promising strategy that can elicit distinct responses in normal cells compared to tumor cells. These dietary strategies can alter the circulating levels of various hormones and metabolites, including blood glucose, insulin, glucagon, growth hormone, insulin-like growth factor, glucocorticoids, and epinephrine, thereby potentially exerting an anticancer effect. Additionally, elevated levels of insulin-like growth factor-binding proteins and ketone bodies may increase tumor cells’ dependence on their own metabolites, ultimately leading to their apoptosis. The combination of fasting or fasting-mimicking diets with radiotherapy or chemotherapeutic agents has demonstrated enhanced anticancer efficacy. This paper aims to classify fasting, elucidate the mechanisms that underlie its effects, assess its impact on various cancer types, and discuss its clinical applications. We will underscore the differential effects of fasting on normal and cancer cells, the mechanisms responsible for these effects, and the imperative for clinical implementation.